Cita Demokrasi Indonesia dalam Politik Hukum Pengawasan Dewan Perwakilan Rakyat terhadap Pemerintah - Ridlwan, Zulkarnain (Mahkamah Konstitusi Republik Indonesia, 2015)
Constitutional discourse can not be separated from the discussion on democracy building. The existence of the House of Representatives in Indonesia with its oversight function of government is one manifestation of democracy. With a historical approach juridical writings results of this study concluded that the statute law of political representative institutions is likely to continue to strengthen parliamentary oversight of government functions by providing additional instruments that can be used by the legislature as an institution and the individual members of the House to conduct oversight. The legal political tendencies are in accordance with the ideals of democracy in Indonesia who wanted representation of the people in the context of the embodiment of the people’s sovereignty in a representative body, but does not eliminate the critical power of the people to the ruler.